AI Arms Races: Implications for Global Stability (Journal of Computational Intelligence and Robotics, 2021)
This study explores the emerging impact of artificial intelligence (AI) technologies on global military dynamics, focusing on how the adoption of AI systems in the defense domain can catalyze new arms races. The implications of these trends for global stability are assessed, identifying specific risks associated with escalation, strategic instability, and the erosion of international norms. Finally, governance and arms control strategies designed to mitigate these risks in the context of international security are proposed.The integration of artificial intelligence (AI) technologies into military arsenals has ushered in a new era of arms races, with profound implications for global stability. This article examines how the adoption of AI in military applications is redefining defense strategies, accelerating weapons competitions, and posing unique challenges to international security. Through multidisciplinary analysis, risks of escalation and strategic instability are explored, and a framework for governance and arms control adapted to the AI era is proposed.